OBSERVATION ON THE AVIFAUNA OF SIBERUT ISLAND, 1992-1994 - ASEP S. ADHIKERANA (BRIN Publishing (Penerbit BRIN), 1994)
The recent studies were carried out in 1992-1994, and aimed at investigating recent status and distribution of the avifauna of Siberut Island. Ninety-six species were recorded during the observations, of which all endemic subspecies and one endemic species were observed. From all species, 11.5% were very common and 37.5% were common in the island, while 28.1 % of them were uncommon and22.9% were rarely found. Protected and endemic species were amongt the rarely found birds, except the nectar feeding birds which were abundant in the island. Most of these birds might have functioned as either secondary or tertiary consumers, which are vulnerable to habitat deterioration. Habitat conservation may be the best measures to be considered.